Implementation of “Outbound Green Class” Program as a Way to Increased English Language Ability and interest of reading activity for Children and Adolescents at Makassar City - Musdalifah Ifah Rahman; Ismaya Ismaya; Elihami Elihami (LP2M Universitas Muhammadiyah Enrekang, 2020)
Community Service Activities (PKM) about “Outbound Green Class” program was one of the newest programs that the author applied in her English course place. She carried out this activity in collaboration with several her friends and who have same profession with her that was English lecturer.